Friendship quality among autistic and non-autistic (pre-) adolescents: Protective or risk factor for mental health?. (November 2022) - O'Connor, Rachel A.G.; van den Bedem, Neeltje; Blijd-Hoogewys, Els M.A.; Stockmann, Lex; Rieffe, Carolien
Autistic (pre-) adolescents are often misunderstood by their peers, which can lead to challenges within their friendships. Yet, friendships play an important role in our psychological wellbeing, whereby in the non-autistic population good quality friendships usually protect against mental health difficulties, whereas conflictual friendships increase the risk. The present study investigated positive and negative friendship quality in autistic and non-autistic (pre-) adolescents. Furthermore, the relations between positive friendship quality and negative friendship quality with anxiety and depressive symptoms were examined. Participants were 306 autistic and non-autistic (pre-) adolescents aged 9–16 ( M  = 11.69 years; SD  = 1.33 years). Our results demonstrated that autistic (pre-) adolescents reported lower positive friendship quality than their non-autistic peers, while no group or gender differences were observed for negative friendship quality than non-autistic boys. For the whole sample, positive friendship quality was associated with fewer depressive symptoms, while the opposite was true for negative friendship quality. For autistic girls only, higher positive friendship quality was related to more symptoms of anxiety. These outcomes seem to emphasize the need for supporting the friendships of autistic young people, perhaps by educating non-autistic young people around how to be supportive friends to their autistic peers. Lay abstract: Autistic young people are often misunderstood by non-autistic young people, and this can lead to difficulties in their friendships. We know that friendship is very important for our mental health. For non-autistic young people, having good friendships is linked to better mental health and having problems in friendship can cause mental health problems. This study aimed to compare the positive and negative features of friendship that autistic non-autistic young people experience. The study also aimed to understand if having positive or negative friendship features is related to signs of mental health problems (anxiety and depression). 306 young people aged 9–16 took part in this study. These were 86 autistic boys, 18 autistic girls, 91 non-autistic boys and 111 non-autistic girls. The findings of this study showed that autistic young people have less positive friendship features than non-autistic young people. For all young people in the study, having more positive friendship features was related to fewer signs of depression, while having more negative friendship features was related to more signs of depression. Just for autistic girls, having more positive friendship features was related to more signs of anxiety. These findings show that support is needed to help autistic young people have more positive friendships. For example, by teaching non-autistic young people how to be supportive friends to their autistic peers.